Determinants of demand for credit: A conceptual review - Kofarmata, Yusuf Ibrahim; Applanaidu, Shri Dewi; Hassan, Sallahuddin (Asian Online Journal Publishing Group, 2016)
It is generally agreed among the researchers that farm credit has significant positive impact on agricultural production that would increase the farming output.In fact, the rising cereal production were more related to farm inputs that may be acquired through agricultural credit.In view of that, this article synthesizes and reviews different field studies on the determinants of demand for credit.Moreover, it is clear from the reviewed studies that different models have been used in examining the factors that determine the demand for credit.However, most of the findings are inconclusive, due to the contextual, geographical, socio-economic, environmental and other variations across the study areas. Based on that, the paper call the need for more empirical studies on the determinants of demand for credit for a specific region for better policy that may be suitable for that particular region.This has important implications on agricultural production in general and farm credit in particular, especially for developing economies.